2013
DOI: 10.1007/s10457-013-9640-y
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly distribution in fragmented landscapes containing agroforestry practices in Southeastern Brazil

Abstract: Agroforestry practices, such as Shaded Coffee and Homegardens, may provide habitat for forest butterflies and contribute to their conservation in fragmented agricultural landscapes. To determine the influence of agroforestry practices in an agricultural mosaic, the distribution of fruit-feeding butterflies was studied using a systematic approach that compared butterfly species richness in six land-use practices (Eucalyptus [Eucalyptus spp.], Shaded Coffee, Homegardens, Secondary Growth, Pastures, and monocultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 60 publications
2
16
1
3
Order By: Relevance
“…An intensive mark-release-recapture study in Papa New Guinea showed that many tropical butterflies can disperse up to 1 km from their larval host plant (Vlasanek et al 2013), so the presence of adult butterflies within SMCF and timber plantation does not guarantee that these habitats in isolation could support the observed butterfly diversity. This is consistent with our finding that butterfly abundance and diversity both decreased with distance from natural forest, with diversity declining by more than half over distances >500 m. Other studies in tropical agricultural landscapes have found that agricultural land use has a stronger effect on butterfly diversity than proximity to forest (Perfecto et al 2003, Francesconi et al 2013, but on a wider scale, isolation from contiguous forest is negatively correlated with the species richness of fruit-feeding butterflies in Bornean forest fragments (Benedick et al 2006). Landscape effects are known to impact butterfly meta-population dynamics in temperate systems (Hanski & Thomas 1994, Hill et al 1996, Thomas et al 2001, with occasional immigration from source populations rescuing isolated populations at marginal 'sink' sites from extinction (Hanski & Ovaskainen 2003).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…An intensive mark-release-recapture study in Papa New Guinea showed that many tropical butterflies can disperse up to 1 km from their larval host plant (Vlasanek et al 2013), so the presence of adult butterflies within SMCF and timber plantation does not guarantee that these habitats in isolation could support the observed butterfly diversity. This is consistent with our finding that butterfly abundance and diversity both decreased with distance from natural forest, with diversity declining by more than half over distances >500 m. Other studies in tropical agricultural landscapes have found that agricultural land use has a stronger effect on butterfly diversity than proximity to forest (Perfecto et al 2003, Francesconi et al 2013, but on a wider scale, isolation from contiguous forest is negatively correlated with the species richness of fruit-feeding butterflies in Bornean forest fragments (Benedick et al 2006). Landscape effects are known to impact butterfly meta-population dynamics in temperate systems (Hanski & Thomas 1994, Hill et al 1996, Thomas et al 2001, with occasional immigration from source populations rescuing isolated populations at marginal 'sink' sites from extinction (Hanski & Ovaskainen 2003).…”
Section: Discussionsupporting
confidence: 92%
“…, Francesconi et al . ), but on a wider scale, isolation from contiguous forest is negatively correlated with the species richness of fruit‐feeding butterflies in Bornean forest fragments (Benedick et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also interesting to note that we classified Mycalesis terminus as a forest specialist while two other Mycalesis species ( M. perseus and M. sirius ) are mainly found in sugarcane plantations. This evidence, which has also been found for other sister species in Guyana by Sambhu et al (), is contrary to the notion that similar species behave or live in similar areas (Francesconi et al, ). Nonetheless, the unique compositions of forest habitats suggest that conservation of these habitats may target different species than conservation of human‐modified habitats.…”
Section: Discussioncontrasting
confidence: 64%